Hydraulic properties of compacted residual soils by indirect method - Ng, Darren. (2009)
Permeability function of unsaturated residual soil is an important property that governs water movement. Permeability determination of unsaturated soils using direct measurement is a tedious and time-consuming process, especially at low water content conditions. Indirect measurement was used in the study. Unlike saturated soils, the permeability of unsaturated soils is a function of both void ratio and water content. Changes in these two parameters will significantly affect the permeability of the unsaturated soils. Soil samples were compacted at three compaction efforts using the standard Proctor hammer to determine how compaction efforts affect the soil fabric and void ratio and hence the effect the permeability of unsaturated soils. To determine the soil-water characteristic curve (SWCC), compacted soil samples were saturated and saturated permeabilities were measured before pressure plate tests were conducted. Both the drying and wetting SWCCs were obtained. A program ACUPIM/W was used to determine the permeability function through the input of the saturated permeability and the SWCC. Results showed that soils compacted at dry of optimum have higher saturated permeability than those at wet of optimum. The pore structure of the soils proved to have a more significant effect on the saturated permeability than void ratio. Comparison of the unsaturated coefficients of permeability obtained from ACUPIM/W with those obtained from disk infiltrometer tests showed reasonable agreement where the differences were within one order.